Intraoral hydatid cyst: A rare case report - Ravi Kiran Alaparthi; Samatha Yelamanchili; Purnachandrarao Naik Nunsavathu; Udaya Sode (Wolters Kluwer Medknow Publications, 2015)
"Hydatid" is a Greek word which means "a drop of water." Hydatid cysts occur in hydatid disease or echinococcosis, which is one of the most geographically prevalent zoonosis. This zoonotic infection in humans is mainly caused by infection by the larval stage of the dog tapeworm Echinococcus granulosus. This tapeworm infestation is widespread in sheep, goats, cattle, and dogs. This chronic disease is present worldwide among herding populations who live in close proximity to dogs and herd animals. It is a serious and potentially fatal condition and symptoms may occur a long time after the early infection. The most frequently affected organs are liver, lungs, followed by bones and brain, and extremely unusual occurrence has been found in the oral cavity, which was noticed in the present case. So hereby, we reveal a very rare case of intraoral hydatid cyst in a 20-year-old female patient.